Manajemen Strategis Kepala Sekolah dalam Mewujudkan Daya Saing Sekolah (Studi Kasus pada SMP Swasta Muhammadiyah Sidikalang Kab. Dairi) - Rahmadani Hasibuan (Journal on Education, 2023)
Education that is able to develop human resources to meet the demands of the developing era. The aim of this research is to reveal and describe the analysis of the school environment, strategic planning, strategic implementation, monitoring and assessment, and school quality. Based on the problem focus, objectives and characteristics, the approach used in this research is a qualitative approach with qualitative descriptive methods. The research results found that the implementation of strategic management was not perfectly in accordance with the provisions. The factors of strength, weakness, opportunities and threats that are the basis for strategic formulation in creating quality schools have not used SWOT analysis, that is, they have not used SO, WO, ST and WT strategies. There are still several activities in strategic implementation in the form of developing programs, budgets and procedures, as well as strategic monitoring and assessment that have not run optimally, so that the formation of outputs in the form of creating quality schools and quality graduate outcomes still needs to be developed optimally and consistently. However, the quality of the school is reflected in the school's predicate of always being accredited "A", having various achievements in both academic and non-academic fields at various levels, meeting the criteria for 8 national education standards, as well as services in the form of continuously improving processes, continuing to make mistakes. reduced, work discipline increases, control takes place more effectively which is ultimately expected to satisfy customers.